CP-161 A clinical and cost analysis of medication reconciliation by pharmacists at discharge from the acute medical assessment unit (AMAU) of a large urban teaching hospital. (25th February 2017) - Gavin, C; Carr, B; Sahm, L
Abstract : Background: The transition between primary and secondary care is one of the most common points of medication errors, with much published information relating to errors at admission. There is currently a lack of comprehensive data on the prevalence and severity of medication errors occurring at the point of discharge and the impact of these errors on both patient safety and healthcare expenses, along with the role of the pharmacist in reducing these. Purpose: The aim of this study was to assess the impact of a pharmacist discharge service within the acute medical admission unit (AMAU). This was achieved by (i) quantifying and categorising the unintentional medication variances, (ii) assessing the potential patient safety benefits using a validated tool and (iii) estimating the cost of providing a pharmacist discharge service and the cost avoided. Material and methods: A medication reconciliation at discharge was conducted by the clinical pharmacist once completed by the medical team. A seven member peer review panel reviewed the interventions using the visual analogue scale (VAS) validated severity tool to assess the potential patient harm and the potential for readmission. Cost avoidance was then calculated per intervention by linking VAS scores to a monetary value. Results: 71 patient discharges with 146 interventions were reviewed. 83.1% of discharges required an accepted pharmacist intervention. 72.6% of interventions related to 'prescription errors' and 27.4% related to 'communication errors'. 26.7% of the interventions were classified as minor (<3) with no patient harm expected. The majority (71.2%) were classified as moderate to serious (3–7) potential to cause patient harm. 2.1% of the interventions were classified as potentially severe (8–10). The potential to prevent readmission was moderately likely in 48% of interventions. The estimated total cost avoidance was €107.45 per intervention and a cost:benefit ratio of 59.50:1 was calculated. Conclusion: A pharmacist discharge service was shown to have a hugely positive effect in terms of patient safety and cost avoidance to the hospital. These results will inform the expansion of the pharmacist role in the study hospital. References and/or acknowledgements: Acknowledgements to the members of the peer review panel: Dr Declan Byrne, Dr Elizabeth Mc Carron, Dr Eileen Relihan, Fiona Kelly and Lorraine Glynn. No conflict of interest